YOUTH AND ADULT EDUCATION: ITS RELEVANCE TODAY - Risia Gonçalves Rios, Rejane; Sales de Oliveira, Michelle (Revista Gênero e Interdisciplinaridade, 2025)
Youth and Adult Education (EJA) is an essential educational modality for those who did not have access to or continued schooling at the appropriate age. This article aims to discuss the importance of EJA in contemporary times, its challenges, and its future prospects, based on an analysis of official documents and theoretical frameworks in the field.